Implantation of a Recycling Plant in the city of Rio Piracicaba-MG (Research, Society and Development, 2019)
The disposal and reuse of waste is one of the main environmental challenges to be overcome by modern society in order to reconcile the objectives of sustainable development and environmental preservation. In Brazil, it is from garbage dumps and on city streets that thousands of people collect and market recyclable materials and in many cases feed on what they collect. In the city of Rio Piracicaba-MG, we have a long history of accidents, among them some fatal, occurred in the dump before located in the locality called "Batatinha". Currently the garbage collected in the city is transported to the landfill located between the city of Rio Piracicaba and João Monlevade, built through an agreement between the cities of Nova Era, Rio Piracicaba, Bela Vista de Minas, São Domingos do Prata and João Monlevade. There is also ASCARIPI, which collects recyclable solid waste in the municipality. Even with the existence of the same, much of the recyclable materials end up in the sanitary landfill, which after 12 years of operation is above half of its capacity of operation. In view of the above, the objective of this project is the implantation of a recycling plant in the city of Rio Piracicaba-MG, which aims to make possible a greater knowledge of a specific problem and seek solution for it. A number of progress has already been achieved, such as the release of funds from the Ministry of the Environment, the location of the site, where the physical space of the plant will be built and trainees hired to carry out environmental education projects in public schools in the municipality. The methodology of this project unfolds in three stages: analysis of the current situation of the collection and disposal of the city garbage; analysis of the possibilities, positive and negative and negative points of the implantation of a recycling plant in the municipality, focused and discovered to knowledge on textual bases and research and still in progress, describe the place of implantation, human resources, machinery, economic and financial organization recycling plant. Legislation has been an important and effective alliance of the environment, at a time when relations between public power and society are under review. Focused on such ideas, this project aims to organize collectors to rationalize selective collection and sorting, reduce costs, increase the flow of recyclable materials and encourage society to adopt ecologically sound conduct through environmental education.